2016
DOI: 10.1186/s13068-016-0674-z
|View full text |Cite
|
Sign up to set email alerts
|

A polysaccharide utilization locus from Flavobacterium johnsoniae enables conversion of recalcitrant chitin

Abstract: BackgroundChitin is the second most abundant polysaccharide on earth and as such a great target for bioconversion applications. The phylum Bacteroidetes is one of nature’s most ubiquitous bacterial lineages and is essential in the global carbon cycle with many members being highly efficient degraders of complex carbohydrates. However, despite their specialist reputation in carbohydrate conversion, mechanisms for degrading recalcitrant crystalline polysaccharides such as chitin and cellulose are hitherto unknow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 43 publications
(59 reference statements)
5
85
0
Order By: Relevance
“…In this study, we found that: (i) the mfsA mutant showed no glucose uptake; (ii) the mfsA mutant did not utilize glucose for its growth; and (iii) the mfsA gene complemented the glucose‐negative phenotype of E. coli LJ141. The present findings in combination with previous findings strongly indicate that mfsA (Fjoh_4565, which is one of the eight above‐mentioned genes) encodes the sole glucose transporter in F. johnsoniae. Comparison with proteins in the MFS family using the International Union of Biochemistry and Molecular Biology (IUBMB) approved Transporter Classification Database (http://www.tcbd.org) revealed that a protein most similar to MfsA is glucose/galactose transporter Ggp (2.A.1.7.2) in Brucella abortus , which belongs to the fucose:H+ symporter (FHS) family (2.A.1.7) and that the top 13 proteins similar to MfsA belong to the FHS family.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, we found that: (i) the mfsA mutant showed no glucose uptake; (ii) the mfsA mutant did not utilize glucose for its growth; and (iii) the mfsA gene complemented the glucose‐negative phenotype of E. coli LJ141. The present findings in combination with previous findings strongly indicate that mfsA (Fjoh_4565, which is one of the eight above‐mentioned genes) encodes the sole glucose transporter in F. johnsoniae. Comparison with proteins in the MFS family using the International Union of Biochemistry and Molecular Biology (IUBMB) approved Transporter Classification Database (http://www.tcbd.org) revealed that a protein most similar to MfsA is glucose/galactose transporter Ggp (2.A.1.7.2) in Brucella abortus , which belongs to the fucose:H+ symporter (FHS) family (2.A.1.7) and that the top 13 proteins similar to MfsA belong to the FHS family.…”
Section: Discussionsupporting
confidence: 89%
“…A recent study by Larsbrink et al . identified a locus containing mfsA and 10 other genes that were involved in F. johnsoniae chitin utilization; mfsA was shown to be required for growth on glucose, N ‐acetylglucosamine, and chitin. Our results confirm and extend these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the detailed genetic, biochemical, and enzyme structural characterization of a galactomannanspecific PUL from B. ovatus revealed the interplay of two mannan-specific SGBPs, two GH26 endo-␤-mannanases, and a GH36 exo-␣-galactosidase in the deconstruction of this plant cell wall polysaccharide (110,111). Among environmental bacteria, a complex chitin utilization locus from Flavobacterium johnsoniae has been extensively functionally characterized (112). Notable features of the system include two pairs of SusC/SusD homologs, a secreted chitinase composed of two GH18 modules separated by a chitin-binding module, and an intracellular glucosamine-6-phosphate deaminase.…”
Section: Insight From Integrated Functional Characterizationmentioning
confidence: 99%
“…seawater, freshwater, wastewater, sediments, marine sediment, rhizosphere soil, alga, compost, glacier and plant [4], suggesting that Flavobacterium strains were ubiquitous in diverse terrestrial and aquatic environments. Some Flavobacterium strains were found to be able to degrade chitin [12], polysaccharide [13], diesel [14], and pesticide [15], as well as to suppress plant pathogen [16], suggesting that Flavobacterium strains play a vital role in the ecosystem. Therefore, the study of characterization for Flavobacterium strains isolated from saline-alkaline may help us to understand the roles of Flavobacterium in the ecosystem of saline soil.…”
Section: Introductionmentioning
confidence: 99%